EVALUASI JARINGAN DALAM STUDI IN VIVO PEMBERIAN EKSTRAK PROPOLIS PADA MODEL LUKA INFEKSI - Winona May Hendrata; Willy Sandhika; Agung Dwi Wahyu Widodo (Majalah Biomorfologi, 2019)
Background: Infection in wound could lead to various consequences including scarring and occurrence of sepsis. With increasing prevalence of resistant strain bacteria, option for treating infected wound need to be constantly expanded. Propolis, a product of honey bee, is a potential treatment which has been studied to have various effects including antibacterial, anti-inflammatory, and antioxidant. Objective: The study aims to assess the effect of propolis toward wound healing, by evaluating wound macroscopic and microscopic appearance. Material and method: Propolis extract were made using maceration technique using ethanol. Thirty Rattus norvegicus male rats were divided into six groups: three groups for treatment and three groups for control. Incision wound were made in the back and was infected with Methicillin ResistantStaphylococcus aureus (MRSA). Propolis was administered orally on daily basis. Wound excision for observation were done on day3, 5, and 7. The tissue were processed using haematoxylin-eosin (HE) staining for microscopic observation. The distance of normal tissue surrounding the wound were measured using image analysis program. Result: Macroscopic observation showed fewer visible wound in the propolis extract treated group. Measurement by microscopic observation on day 3 also demonstrated more narrow wound width in propolis extract treated group (405.75  110.11 μ) compared to the control group (806.20 644.41μ). Conclusion: The result of this study suggests that propolis extract by oral administration promotes the healing of infected wound as shown within microscopic and microscopic observation.